2021
DOI: 10.1016/j.mjafi.2020.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Probable vertical transmission of severe acute respiratory syndrome coronavirus 2 infection from mother to neonate

Abstract: The pandemic spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has affected 188 countries and territories. Altered physiological status during pregnancy makes a mother vulnerable to severe SARS-CoV-2 infection. The virus may be transmitted from mother to baby during antenatal period or postnatal period. Although the primary mode of transmission of the virus is by respiratory droplets, there is emerging evidence of in utero transmission from mother to foetus. In this rare case rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
3
Order By: Relevance
“…The prevalence of placental infection in COVID-19-positive women is low (7.7–21%) [ 73 ]⁠.A few studies have demonstrated SARS-CoV-2 placental infection diagnosis by ISH, IHC, RT-PCR, and transmission electron microscopy (TEM) [ 11 , 15 , 31 , 34 , 52 , 53 , 58 , 61 , 62 , 64 , 65 , 67 , 71 , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] ]⁠. Viral RNA, proteins, and particles were mainly localized in the syncytiotrophoblasts [ 52 , 58 , 61 , 62 , 64 , 80 , 81 , 86 ]⁠.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of placental infection in COVID-19-positive women is low (7.7–21%) [ 73 ]⁠.A few studies have demonstrated SARS-CoV-2 placental infection diagnosis by ISH, IHC, RT-PCR, and transmission electron microscopy (TEM) [ 11 , 15 , 31 , 34 , 52 , 53 , 58 , 61 , 62 , 64 , 65 , 67 , 71 , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] ]⁠. Viral RNA, proteins, and particles were mainly localized in the syncytiotrophoblasts [ 52 , 58 , 61 , 62 , 64 , 80 , 81 , 86 ]⁠.…”
Section: Resultsmentioning
confidence: 99%
“…Gross investigations of placentas from COVID-19-positive mothers were rarely or incompletely reported. A few studies reported normal gross placenta morphology [ 52 , 64 , 76 , 92 ]⁠, but others found adherent clots and focal infarcts [ 58 , 65 , 74 , 89 ]⁠. Weights of second and third-trimester placentas from COVID-19 positive mothers had conflicting results.…”
Section: Resultsmentioning
confidence: 99%
“…Un total de 22 madres embarazadas fueron incluidas en los estudios de caso clínico, de las cuales, 21 dieron resultado positivo a la prueba PCR nasofaríngea diagnosticando COVID-19. Las 22 mujeres eran primigestas; 14,16,18,20,22,24 tres padecían hipotiroidismo; 14,15,18 4% anorexia 14 y 4% anemia.…”
Section: Factores De Riesgo De La Transmisión Verticalunclassified
“…12,14,[16][17][18][19][20][21]24 De los embarazos analizados, nacieron 22 neonatos, de los cuales 14 dieron positivo a la prueba PCR nasofaríngea. Se tomaron en cuenta otras pruebas PCR para la afirmación de transmisión vertical; entre estas se analizó el fluido amniótico que se reportó positivo en el 23%; 14,15,19,20,25 cordón umbilical en el 9% y placenta en el 14%.…”
Section: Factores De Riesgo De La Transmisión Verticalunclassified
See 1 more Smart Citation